The Reward Re‐Training protocol: A novel intervention approach designed to alter the reward imbalance contributing to binge eating during COVID‐19. Issue 7 (28th April 2021) - Juarascio, Adrienne S.; Michael, Megan L.; Srivastava, Paakhi; Manasse, Stephanie M.; Drexler, Sarah; Felonis, Christina R.
Abstract: Reduced exposure to social reward during the COVID‐19 pandemic may result in both reduced reward response to day‐to‐day life activities and elevated reward response to substances or naturally rewarding stimuli (e.g., food). The combined hypo‐ and hyper‐reward responses results in a reward imbalance, which has been noted as a relevant maintenance factor for eating disorders (EDs) characterized by binge eating. This registered report describes the protocol for a pilot randomized controlled trial (RCT) comparing supportive therapy to a novel treatment targeting reward imbalance (Reward Re‐Training; RRT) for individuals with binge eating. Aims of the current study include to confirm feasibility and acceptability of RRT, to evaluate the ability of RRT to engage critical targets, and to provide preliminary estimates of efficacy in reducing ED symptoms at both posttreatment and 3‐month follow‐up. Sixty participants will be randomized to either RRT or supportive therapy. For both conditions, treatment will be delivered in 10 weekly group outpatient therapy sessions conducted remotely using videoconferencing software. Assessments will be conducted at baseline, mid‐treatment, posttreatment, and 3‐month follow‐up to measure feasibility, acceptability, critical treatment targets (i.e., reward to day‐to‐day life activities, reward to palatable foods, social isolation, and loneliness), and ED symptoms.